The Concept of Education in English and Uzbek Proverbs (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the significance of Uzbek and English proverbs considering the similarities and differences of education will be released. Also, this article examines linguistic and cultural aspects of proverbs in both Uzbek and English. This article discusses the role and significance of proverbs in human life as well as the clear and comprehensive conclusions drawn from the work and research of well-known authors, academics, and scientists on the subject of proverbs' cultural and linguistic analysis.